Effect of spacing and skew-angle on clear-water scour at pier alignments - Lança, Rui (2014)
Pier alignments, defined as single-row pier groups, displayed normal to main bridges’ axes, are frequently used to support bridge decks. Different alignments configurations, characterized by different combinations of piers’ shape and spacing and skew-angle of the alignment to the flow direction, lead to different interactions with the flow field and to different scour depths. Twenty six long lasting – 7 to 15 days – laboratory experiments were run under steady clear-water flow conditions, close to the threshold condition of beginning of sediment motion, to address the effect of pier spacing and skew-angle on the equilibrium scour depth. Alignments consisted of four cylindrical piers spaced of 1, 2, 3, 4.5 and 6 pier diameters; tested skew-angles were 0◦, 15◦, 30◦, 45◦ and 90◦. The main contribution of the paper derives from the long duration of the experiments. The functional relation of issued equilibrium scour depth with pier spacing and skew-angle is established and the dependence of the traditional group correction factor on the same variables is defined.